THE ROLE OF EDUCATORS AND PARENTS IN INSTILLING RELIGIOUS AND MORAL VALUES IN EARLY CHILDREN IN THE DIGITALIZATION ERA - Novi Cynthia Yusnita; Putri Sari Ulfa Sembiring; Afdhalina Afdhalina; Abdul Zebar; Afridiani Pulungan (Jurnal Scientia, 2023)
This research is motivated by the large number of children whose behavior is not in accordance with the religious and moral values ​​that have been taught. This is caused by the lack of instilling religious and moral values ​​in children from an early age. The purpose of this study was to determine the role of parents in instilling religious and moral values ​​in early childhood in the digitalization era. This type of research is a qualitative using a descriptive method, namely the description of the situation experienced. Data collection used in the form of interviews, observation and documentation. The results of this study are that parents and teachers use several methods in instilling religious and moral values ​​in early childhood, namely 1) exemplary methods; 2) habituation method; 3) advice method; 4) storytelling method. Educators and parents have roles in their respective environments. Educators play more of a role in the school environment, while parents play more of a role in the home environment. However, both of them continue to work together so that children can have good religious and moral values ​​in this digitalization era.